Performance of Concentrate Supplementation during Pre-partum and Lactation in Sonadi Sheep - Yadav, C. M.; Sharma, R. K. (International Journal of Livestock Research, 2019)
An on-farm trial was undertaken to assess birth weight, milk intake and growth performance of Sonadi sheep in field condition maintained on grazing alone (T1) and supplemented graded levels of concentrate feed (10 and 20% of dry matter requirements) during late gestation (last 45 days of gestation) and lactation (first 60 days of lactation) in T2 and T3 groups. Lambs were fed concentrate feed @ 10 and 20% of the dry matter requirements up to 120 days in T2 and T3 groups, respectively. The significantly (P<0.05) different body weight gains in Sonadi sheep during late gestation in T1, T2 and T3 groups was observed and values were 1.05+0.32, 1.33+0.16 and 2.15+0.22 kg, respectively. Birth weight of lambs in 2.84+0.06 (T3) and 2.21+0.05 (T2) groups were significantly (P<0.05) higher than 1.89+0.76 (T1) group. Similarly, milk intake of lambs in T3 and T2 groups were significantly (P<0.05) higher as compare to T1 group. It was concluded that supplementation of concentrate feed to adult Sonadi sheep @ 20% of dry matter requirement during late gestation and lactation not only improves the body weight of ewes but also increases the birth weight and the milk intake and subsequent growth rate of lambs.